Web Services for Mobile Devices from One Server - Yesiltepe, Mirsat (IEEE, 2018)
Mobile devices used for communication between people only for speaking people in the past but today one of the most personal kind devices in the cloud environment [1]. The environment is expanding day by day via accessibility connecting internet with devices. The device can be any kind of device if it has the ability working with web. The transaction should be with sending and receiving messages [2]. Mobile devices can connect the cloud also [3]. This article aims answering the question Is cloud environment server its system equally for any kind of mobile devices which has different operation system?, throttling mechanism for mobile world which has the devices with multiple cores and push services for mobile devices. In this paper, will be discussed two mobile operations, which are Windows Phone and Android because of comparison of open source and secret sauce. Push services, the use of different protocols in the same environment with the resulting differences and message level security issues are another issue discussed in the paper.
Keywords: mobile devices; message level security; throttling mechanism; protocol; Engineering; Telecommunications